Belgian Radiology Research in Full Power!. Issue 1 (27th February 2017) - Vanhoenacker, Piet
In Belgium, there has always been a strong tradition to foster radiology and imaging research. The former Royal Belgian Society of Radiology (RBSR-KBVR-SRBR)—after the merger with the Consilium and NUR, now the Belgian Society of Radiology (BSR-BVR-SBR)—has persistently been one of the driving forces of support to individuals who wanted to innovate and put Belgian radiology research at the forefront.